Phytochemical characterization and bioinformatics guided evaluation of antioxidant and cytotoxic effects of Psoralea bituminosa - Nour H. Aboalhaija; Rima Hajjo; Fatma Afifi; Heba Syaj; Rana Abu-Dahab (Scientific Reports)
Abstract Psoralea bituminosa L. (Fabaceae) is a medicinal plant traditionally used for its antimicrobial, antihyperglycemic, and antioxidant effects. This study investigated its anticancer and antioxidant potential using aqueous and methanol extracts. The methanol extract exhibited higher total phenol (81.57 mg/g) and total flavonoid (39.06 mg/g) contents compared to the aqueous extract. Antioxidant activity, assessed via the DPPH assay, showed moderate potency (IC₅₀: 330.77 µg/mL for aqueous- and 348.27 µg/mL for methanol extracts). Notably, the methanol extract demonstrated significant cytotoxicity against multiple cancer cell lines (IC₅₀: 27.73–53.90 µg/mL) particularly against A549, MDA-MB231, and PC3. Liquid chromatography-mass spectrometry (LC-MS) profiling revealed abundant flavonoids and isoflavones such as daidzein, biochanin A, and 7,3’-dimethoxy-5,6,4’ trihydroxyisoflavone in the methanol extract, correlating with its anticancer effects. In contrast, glycosylated flavonoids in the aqueous extract aligned with antioxidant activity. Cheminformatics clustering supported these findings, identifying distinct structural groups with differing drug-likeness scores. Bioinformatics analysis further identified transcriptomic signatures enriched in oxidative phosphorylation and key cancer-related pathways (e.g., TP53, PI3K, NRF2, and MYC), offering mechanistic insight. This integrative approach combining LC-MS, cheminformatics, and bioinformatics provides a cost-effective framework for decoding phytochemical bioactivity and guiding natural product-based drug discovery.